2015
DOI: 10.1108/ijlss-07-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Combining Lean and Six Sigma in the context of Systems Engineering design

Abstract: Purpose – The purpose of this paper is to present a combined framework for system design using Six Sigma and Lean concepts. Systems Engineering has evolved independently and there are numerous tools and techniques available to address issues that may arise in the design of systems. In the context of systems design, the application of Six Sigma and Lean concepts results in a flexible and adaptable framework. A combined framework is presented here that allows better visualization of the system-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The PDCA-cored LSS framework Different from the proponents of DMAIC-cored LSS implementation frameworks, some scholars propose to use lean tools as the core structure of LSS implementation frameworks (George, 2003;Sreeram and Thondiyath, 2015;Chakravorty and Hales, 2017). Industrial practices show that some companies instead prefer to use non-structured lean tools such as VSM as the core structure.…”
Section: Lean Six Sigmamentioning
confidence: 99%
See 1 more Smart Citation
“…The PDCA-cored LSS framework Different from the proponents of DMAIC-cored LSS implementation frameworks, some scholars propose to use lean tools as the core structure of LSS implementation frameworks (George, 2003;Sreeram and Thondiyath, 2015;Chakravorty and Hales, 2017). Industrial practices show that some companies instead prefer to use non-structured lean tools such as VSM as the core structure.…”
Section: Lean Six Sigmamentioning
confidence: 99%
“…PDCA has the beauty of simplicity and the power of adaptability, while A3 is effective in facilitating experiential learning (Chakravorty and Hales, 2017), and thinking and leadership development (Shook, 2008). Sreeram and Thondiyath (2015) developed a PDCA-cored LSS framework based on their analysis of three process improvement methodologies: lean, Six Sigma and systems engineering. They concluded that PDCA is the ideal structure for LSS implementation, because of its "flexibility and simplicity […] (such that) any concept/tool from lean, Six Sigma, and Systems Engineering could readily be integrated into this framework (p. 298)".…”
Section: Lean Six Sigmamentioning
confidence: 99%
“…This trend indicates that the level of progress in the LSS domain is very high. Their framework was a revised form of an earlier framework but does not cover the factors related to LSS strategies and toolset required at each phase which reduces its capability 20 Carvalho et al (2014) Their framework was built under five theoretical constructs but fails to explain the role of management, internal and external customer within the execution of LSS 21 Sreeram and Thondiyath (2015) Their framework describes a unique combination of lean and six sigma into a system, but does not shed any light on usage of IT and organisational based factors. It also lacks in presenting the importance of training and education 22 Garza- Reyes (2015) Their framework was built by combining lean with green and later merging into six sigma.…”
Section: Classification Based On Research Requirementsmentioning
confidence: 99%
“…5.1.8 Organisational performance. This construct in the existing LSS frameworks is commonly observed, please refer (Al-Aomar, 2012;Chakraborty and Leyer, 2013;Sreeram and Thondiyath, 2015). These scholars link organisational performance with financial and operating performances.…”
mentioning
confidence: 96%
See 1 more Smart Citation